A Two-parameter Weighted Inverse Lindley Distribution and Applications - Kantalo, Jirawat; Suntornchost, Jiraphan (Journal of Applied Statistics and Information Technology, 2018)
A two-parameter weighted inverse Lindley (TWIL) distribution, of which the inverse Lindley (IL) distribution is a particular case, has been introduced. It’s properties such as survival function, hazard function, moments and other associated measures are obtained. Moreover, parameter estimations of the new distribution by the maximum likelihood estimation (MLE) and the bias-corrected maximum likelihood estimation (CMLE) are also provided. Simulation results and applications to two data sets show that the new distribution outperforms other extensions of the Lindley distribution.